Comparison of DNA Methylation Changes Between the Gestation Period and the After-Delivery State: A Pilot Study of 10 Women - Lin, Ming-Wei; Tsai, Mong-Hsun; Shih, Ching-Yu; Tai, Yi-Yun; Lee, Chien-Nan; Lin, Shin-Yu (Frontiers in Nutrition, 2022)
Background: Gestational adaptation occurs soon after fertilization and continues throughout pregnancy, whereas women return to a pre-pregnancy state after delivery and lactation. However, little is known about the role of DNA methylation in fine-tuning maternal physiology. Understanding the changes in DNA methylation during pregnancy is the first step in clarifying the association of diet, nutrition, and thromboembolism with the changes in DNA methylation. In this study, we investigated whether and how the DNA methylation pattern changes in the three trimesters and after delivery in ten uncomplicated pregnancies. Results: DNA methylation was measured using a Human MethylationEPIC BeadChip. There were 14,018 cytosine-guanine dinucleotide (CpG) sites with statistically significant changes in DNA methylation over the four time periods (p < 0.001). Overall, DNA methylation after delivery was higher than that of the three trimesters (p < 0.001), with the protein ubiquitination pathway being the top canonical pathway involved. We classified the CpG sites into nine groups according to the changes in the three trimesters and found that 38.37% of CpG sites had DNA methylation changes during pregnancy, especially between the first and second trimesters. Conclusion: DNA methylation pattern changes between trimesters, indicating possible involvement in maternal adaptation to pregnancy. Meanwhile, DNA methylation patterns during pregnancy and in the postpartum period were different, implying that puerperium repair may also function through DNA methylation mechanisms.